2009
DOI: 10.3989/gya.130708
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of nitrate and nitrite in dry-cured ham and their effects on aroma development

Abstract: SUMMARY Relevance of nitrate and nitrite in dry-cured ham and their effects on aroma development.Potassium and sodium salts of nitrite (E 249 and E 250) and nitrate (E 251 and E 252) are authorised for use under certain levels in several foodstuffs such as non-heat-treated, cured and dried meat products, other cured meat products, canned meat products and bacon. The key point in the use of nitrate and nitrite as preservatives is to find a balance between ensuring the microbiological safety of the ham and ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
18
0
5
Order By: Relevance
“…It has been postulated that chemical or enzymatic reactions such as lipolysis, chemical or enzymatic oxidation, proteolysis, Strecker degradation and Maillard reactions are present in the dry-curing process of Iberian hams (Narváez-Rivas et al, 2007), and that these chemical processes are the origin of volatile compounds (Toldrá, 1998;Toldrá et al, 2009) which are especially generated in the latest stages (Flores, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that chemical or enzymatic reactions such as lipolysis, chemical or enzymatic oxidation, proteolysis, Strecker degradation and Maillard reactions are present in the dry-curing process of Iberian hams (Narváez-Rivas et al, 2007), and that these chemical processes are the origin of volatile compounds (Toldrá, 1998;Toldrá et al, 2009) which are especially generated in the latest stages (Flores, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Some research showed that ingredient and nitrate/nitrite salt on meat product besides affect color (Honikel, 2008) and flavor (Toldra et al, 2009), also affect oxidation lipid (Sebranek & Bacus, 2007;Toldra et al, 2009). Nitrite added at curing process could form reactive compound NO that could bind to myoglobin and produce heat stable cure color.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that chemical or enzymatic reactions such as lipolysis, chemical or enzymatic oxidation, proteolysis, Strecker degradation and Maillard reactions are the origin of volatile compounds (Toldrá, 1998;Toldrá et al, 2009).…”
Section: Introductionmentioning
confidence: 99%